การใช้โพลีเมอร์นาโนแอมฟิฟิลลิคโพลียูรีเธนในการดูดซับสารออแกนโนคลอรีนจากดินและการพยากรณ์การดูดซับ - เบญจลักษณ์ กาญจนเศรษฐ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
Amphiphilic polyurethane nanoparticles (APU) were synthesized to examine sorption/removal of five organochlorine insecticides including benzene hexachloride, heptachlor, aldrin, dieldrin, endrin, and DDT from soil. Synthesized APU in the most size range of 55-155 nm and with concentration of 10 g. l.[superscript -1] were found most effective and used for the whole experiment. Contact time which allowed APU solution and spiked soil to reach equilibrium was of 48 h exhibited most efficient sorption/removal. The results indicated influencing factors for the sorption were both properties of soil and compounds. Organic carbon and clay contents play important role on the sorption as well as log K[subscript OC] values. Since the testing compounds were not all similar molecular structure, the prediction from their properties were not successful except those of heptachlor, aldrin, dieldrin, endrin which have similar in molecular structures. Log K[subscript OW] and aqueous solubility (S) values in the literature were varied depending on their experimental conditions, therefore no reliable values can be used for the test of their relationships to the sorption activity. In the group of similar molecular structure, MW and sorption was undoubtedly related. The sorption/removal capacity found to be in the range of 85.2-92.8% for all soil samples and in the order of benzene hexachloride>endrin>dieldrin>heptachlor>aldrin>DDT according to their increasing log K[subscript OC].